Interfaith Marriages: Navigating Psychological and Legal Complexities in Light of Religious Norms and National Laws - Aldi Saputra (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The relationship between religious people attracts attention because of the diversity of their communities. Interfaith marriages, especially among the wealthy and celebrities, are becoming a common phenomenon. Liberal views in favour of religious differences in marriage receive attention, but it is important to understand the true views of Islam. This literature research uses literature study methods, evaluating research results, reports, and scientific journals as primary data, as well as legal regulations and books as secondary data. Content analysis is used to obtain an image without the intervention of the researcher. The impact of interfaith marriages, such as psychological and juridical aspects, shows complexity. Islam's ban on interfaith marriage and the Marriage Act asserts the necessity of conforming to religious law. However, social realities can give rise to legal problems of registration of children and division of inheritance. In conclusion, interfaith marriages reflect psychological and legal challenges. A deep understanding of religious norms, national laws, and local community dynamics is crucial for dealing with the complexity of issues that arise. Keywords: Laws on Marriages Different Religions Abstrak Hubungan antar umat beragama menarik perhatian karena keberagaman masyarakatnya. Pernikahan beda agama, terutama di kalangan kaya dan selebriti, menjadi fenomena yang umum. Pandangan liberal yang mendukung perbedaan agama dalam pernikahan mendapat perhatian, namun penting memahami pandangan Islam yang sejati. Penelitian literatur ini menggunakan metode studi literatur, mengevaluasi hasil penelitian, laporan, dan jurnal ilmiah sebagai data primer, serta peraturan hukum dan buku sebagai data sekunder. Analisis isi digunakan untuk mendapatkan gambaran tanpa campur tangan peneliti. Dampak pernikahan beda agama, seperti aspek psikologis dan yuridis, menunjukkan kompleksitas. Larangan Islam terhadap pernikahan lintas agama dan Undang-Undang Perkawinan menegaskan keharusan sesuai dengan hukum agama. Namun, realitas sosial dapat menimbulkan masalah hukum pencatatan anak dan pembagian warisan. Kesimpulannya, pernikahan beda agama mencerminkan tantangan psikologis dan hukum. Pemahaman mendalam terhadap norma agama, hukum nasional, dan dinamika masyarakat setempat krusial untuk menangani kompleksitas isu-isu yang muncul. Kata Kunci: Hukum Tentang Perkawinan Beda Agama